Characters and characterisation in the epic cycle - Thompson, BA (2021)
The aim of this thesis is to use the various characters who play a part in the Epic Cycle as a tool with which to understand more about the Cycle and the pre-Homeric oral tradition. In Part 1, I use characters as a way to approach the different sources of information we have for the Epic Cycle, namely the Bibliotheca of Apollodorus and the various fragments from later writers and scholiasts. I take the view that these sources are, on the whole, less valuable than Proclus’ epitomes. By looking at the characters unique to these accounts, I assess the value and utility of Apollodorus and the fragments for our knowledge of the Epic Cycle. Nevertheless, the thesis also raises questions about the status of Proclus’ epitomes and the extent to which they give us access to the ‘authentic’ Epic Cycle.